IMPLEMENTASI KEBIJAKAN PENGELOLAAN PASAR RAKYAT PADA PASAR BUDURAN KABUPATEN SIDOARJO - Erry Pratama; Diana Hertati (Universitas Halu Oleo, 2021)
The existence of a market is one indicator of the economic activities of the people in an area. This research is motivated by the lack of optimal management of the Buduran Market by the Industry and Trade Office of Sidoarjo Regency. It can be seen from the supporting facilities and infrastructure in the Buduran Markets which are still inadequate and poorly maintained. This study aims to determine how the implementation of community market management policies in Buduran Market, Sidoarjo Regency. The research method used in this article is a descriptive research method with a qualitative approach by using a qualitative approach. The results show that the implementation of the people's market management policy has been implemented, but there are still problems in its implementation. The conclusion of this research is the implementation of the people's market management policy in its implementation is still not optimal, this can be seen from the indicators of the success of policy implementation.